Confidence and Trust is not Built in a Day. Nomura Asset Management and its strategy after the Subprime Financial Crisis - Tsuchiya, Michiko (2008)
This paper analyzes the asset management industry in the current business environment after the economy and the capital markets suffered a financial crisis triggeded by the sub-prime issues. The paper begins with firm analysis where it identifies Nomura Asset Management's key strategic issue and assess the issues of operational process in investment management to illustrate and describe the key strategic issues asset management firms face. Subsequently followed by the industry analysis to incorporate a number of important analysis and discussion regarding asset management firms and its validity to investors in terms of adding value, to examine the validity of the industry. In addition the paper examines and critically analyses the traditional measures of risk and performance used by asset management firms incorporating the rapidly changing global capital market environment, as well as the anomaly caused by the financial crisis such as the effect from financial leverage and gearing, identifying agency issues seen among financial institutions and redefining the responsibilities for asset management firms.